Target 2035 – update on the quest for a probe for every protein. Issue 1 (3rd December 2021) - Müller, Susanne; Ackloo, Suzanne; Al Chawaf, Arij; Al-Lazikani, Bissan; Antolin, Albert; Baell, Jonathan B.; Beck, Hartmut; Beedie, Shaunna; Betz, Ulrich A. K.; Bezerra, Gustavo Arruda; Brennan, Paul E.; Brown, David; et al.
Abstract : Twenty years after the publication of the first draft of the human genome, our knowledge of the human proteome is still fragmented. Target 2035 aims to develop a pharmacological modulator for every protein in the human proteome to fill this gap. Abstract : Twenty years after the publication of the first draft of the human genome, our knowledge of the human proteome is still fragmented. The challenge of translating the wealth of new knowledge from genomics into new medicines is that proteins, and not genes, are the primary executers of biological function. Therefore, much of how biology works in health and disease must be understood through the lens of protein function. Accordingly, a subset of human proteins has been at the heart of research interests of scientists over the centuries, and we have accumulated varying degrees of knowledge about approximately 65% of the human proteome. Nevertheless, a large proportion of proteins in the human proteome (∼35%) remains uncharacterized, and less than 5% of the human proteome has been successfully targeted for drug discovery. This highlights the profound disconnect between our abilities to obtain genetic information and subsequent development of effective medicines. Target 2035 is an international federation of biomedical scientists from the public and private sectors, which aims to address this gap by developing and applying new technologies to create by year 2035 chemogenomic libraries, chemical probes, and/or biological probes for the entire human proteome.